Antecedents of Muslim tourist loyalty: The role of Islamic religiosity and tourist value co-creation - Abror Abror; Dina Patrisia; Yunita Engriani; Yunia Wardi; Rahmad Solling Hamid; Mukhamad Najib; Marhana Mohamed Anuar; Mohamed Battour; Ririn Tri Ratnasari (Cogent Business & Management, 2023)
This research investigates the antecedents of tourist loyalty in the Muslim-friendly tourism context. It examines the link between Islamic tourism destination attributes, service quality, customer engagement, value co-creation, and loyalty. It also highlights the moderating roles of Islamic religiosity. This study is survey research using a questionnaire to 450 Muslim tourists as the respondents. The data were collected using purposive sampling as the sampling method. After several preliminary tests, this study only used 375 usable responses in the analysis. It employed Structural Equation Model (SEM) with AMOS 24 as the software data analysis package. This study revealed that Islamic tourism destination attributes have significant impacts on service quality, customer engagement, and tourist loyalty. It found that service quality and tourist engagement are the antecedents of tourist value co-creation. Value co-creation also has a significant influence on tourist loyalty. Surprisingly, it also highlighted significant moderating impacts of religiosity. This research only focused on the Indonesian context; hence, the findings have limited generalization. Therefore, it may extend to other Muslim or non-Muslim countries which concern with Muslim-friendly tourism. Tourist loyalty has several antecedents which are not addressed in this study. Thus, future studies may address other influence factors, such as tourist sociocultural and psychological factors which relate to tourist loyalty. Finally, the managers have to concern with the tourist religiosity in providing their products or services.
Keywords: 650; Islamic tourism destination attributes; religiosity; responsible consumption; service quality; tourist engagement; tourist loyalty; tourist value co-creation